2019
DOI: 10.1371/journal.pone.0212549
|View full text |Cite
|
Sign up to set email alerts
|

Application of multivariant decision tree technique in high performance football: The female and male corner kick

Abstract: The use of multidimensional statistical technique based on decision trees is of recent application in sports science. In the case of football, this technique has not yet been sufficiently proven. The aim of the present study was to search for different success models for the corners in the FIFA World Cup 2014 and FIFA Women's World Cup 2015. For this, the statistical analysis focused on the search for classification models for the different criteria considered (shot, shot between the three posts and goal), bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 32 publications
3
27
0
6
Order By: Relevance
“…This study also confirms that one of the two most productive methods of machine learning are the decision trees [26]. Previous studies that included machine learning application in soccer used as discriminating variables the participation of star players or not [27], technical variables such as passes or shots [28][29][30] or the previous results in the season [31]. A more current study is the only one found that uses physical variables to establish cut-off points but applied to simulated games [32].…”
Section: Introductionsupporting
confidence: 78%
“…This study also confirms that one of the two most productive methods of machine learning are the decision trees [26]. Previous studies that included machine learning application in soccer used as discriminating variables the participation of star players or not [27], technical variables such as passes or shots [28][29][30] or the previous results in the season [31]. A more current study is the only one found that uses physical variables to establish cut-off points but applied to simulated games [32].…”
Section: Introductionsupporting
confidence: 78%
“…For this, the FIFA Women's World Cup 2015 has been analyzed, where the most representative and highest quality teams and players have met. The main novelties or contributions of this work could be summarized in two: the study and analysis of a sport still lacking robust scientific literature, such as women's football; and a new multivariate technique in the world of football research, such as decision trees, has been put to the test (Maneiro et al, 2019c). A first general approach, the available results allow us to think that significant differences exist between successful and unsuccessful teams regarding the "match status" variable in the three analysis performed.…”
Section: Discussionmentioning
confidence: 99%
“…For this, the chi-square automatic interaction detector (CHAID) was used as a growth method, which consists of a statistical and multidirectional tree algorithm that scans data quickly and efficiently, and creates segments and profiles compared to the desired result. In each step, CHAID chooses the predictor variable that presents the strongest interaction with the explained variable (Maneiro et al, 2019c). The categories of each predictor merge if they are not significantly different from the predictive variable.…”
Section: Statistic Analysismentioning
confidence: 99%
“…There are no two equal matches, nor two identical competitions. Therefore, the flexibilization of motor, technical, tactical and strategic behaviors, concretized in a wide inter and intra-individual variability (Moura et al, 2013;Casal et al, 2016;Maneiro et al, 2019b), will allow the emergence of solutions to changing and unpredictable environmental problems. Adaptation to the environment is essential (Seifert et al, 2016).…”
Section: Introductionmentioning
confidence: 99%